Cultural bias and the retention and organization of verbal information: A developmental perspective - Miller, Paul; Awadie, Nancy Joubran; Ibrahim, Raphiq (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study explores how cultural disposition and education impact the ways individuals assimilate and organize information. Students from two cultural backgrounds (individualist, collectivist) and three levels of education (elementary school, high school and university) were tested in two experiments. Findings from Experiment 1, which used a short-term memory (STM) paradigm, revealed that, contrary to a widely held theory, culture per se does not seem to foster propensities toward the use of particular memory strategies. Experiment 2, which used a concept organization paradigm, suggests that, even if cultural/educational preferences bias individuals approach to information in some regards, such bias is overshadowed by and interacts with other more intuitive predispositions. Findings are discussed from a cultural and educational point of view.